Penerapan Metode Card Sort Dalam Upaya Meningkatkan Keaktifan Siswa SDN Kedungsari 4 - Setiawan, Andika Aji; Octavia, Calista Dyah; Azzarine, Aini Savira; Hajron, Kun Hisnan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The study was conducted at SDN Kedungsari 4, the subjects of this study were teachersand third grade students at SDN Kedungsari 4. The number of students was 30 students,consisting of 22 male students and 8 female students. Data collection techniques usingobservation and tests. The research was divided into 2 cycles, namely cycle 1 and 2. Theresults were cycle 1 57% and cycle 2 79%. Based on the data exposure and discussionobtained from the research results, the conclusion that can be drawn from this researchis that the use of the learning model Card sort in science subjects for class III SDNKedungsari 4 can increase student activity.